Albizzia lebbeck extract mediated synthesis and characterization of zinc oxide nanoparticle - Argade, Pranita A.; Bhutkar, Mangesh A.; Magdum, Chandrakant S. (Raipur Asian Pharma Press, 2019)
ZnO nanoparticles have drawn attention of many researchers in the recent years due to their unique optical and chemical behaviours which can be easily turned by changing the morphology. The present study aims to green synthesis of zinc oxide nanoparticle using Albizzia lebbeck aqueous bark extract and study of characterization of synthesized nanoparticle. synthesis of NP$1 (Bs via eco-friendly routes have become more popular due to low cost, synthesis in ambient atmosphere, non-toxicity, environmental compatibility and easy of applications as the resulting particles were biocompatible and devoid of toxic stabilizers. In the present work, green synthesized ZnO NPs were characterized using UV- visible spectroscopy (UV), Fourier transform infrared spectroscopy (FTIR), X- ray diffraction analysis (XRD), Scanning electron microscopy (SEM), Particle size analysis, Zeta potential. Preliminary confirmation through colour changes of reaction mixture and UV- visible analysis. The UV visible analysis result reveals that an obtained absorption peak at 213nm confirm the formation of Zinc oxide nanoparticles. X- ray diffraction study confirm the crystalline nature of synthesized ZnO NPs. SEM images reveals that particles were hexagonal in nature. The particle size and zeta potential of nanoparticle was found as 65.3nm and -35.7nm respectively. After 3month stability the particle size and zeta potential was fond as 73.4 nm and -31.9 respectively s
Keywords: PHARMACEUTICS